“Enviro School" Education House of Waste Utilization to Create Environmental Care Generation - Lisa Aisa; Sulthon Arif Rakhman; Difa Ashmamillah; Desi Mutiara Fani; Gilang Aji Pradana (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Most of the people at Ciaruteun Ilir Village, Cibungbulang Subdistrict, Bogor District are trashing the river. Population growth and consumption pattern change causes the volume, type, and characteristics of existing waste is increasing, especially household waste. Beside from households, there are also a lot of garbage has coming from the agricultural sectors. The main factors causing the community dispose garbage into the river is the unavailability of landfills, awareness and knowledge of the community related to waste management and utilization is still quite low. Seeing these conditions, the team through the Student Creativity Program for Community Service educate how about the management and utilization of waste named enviro school. Enviro school aims to shape the caring behavior of environmental community through environmental education start from an early age, grouping garbage independently, forming the institution of trash bank, and creating creative products from waste through the creation of vermicompost institutions and handicrafts with functional and economic value with target adult people on Ciaruteun Ilir Village RT 05/03. Enviro school has methods through 7 classes, it is pre class, first class, class, green class, brown class, white class, and enviroducation fair. Based on pre test results conducted at the beginning of the program, only 30.90% of people understand the concept of waste management and utulization, then an increase after four months running through the post test of 92.69%. Successfully this program visible from the increased awareness and knowledge about management and utulization of waste, the establishment of enviro trash bank as a structural institution for waste management, increased youth skills in the utilization of organic waste become vermicompost, and increasing skills of mothers in the utilization of anorganic waste.